Empowerment of Red Brick Producers in Preventing Extreme Poverty in Tanggung Village, Malang Regency - Rohmatullah, Muhammad Ali (Amaluna: Jurnal Pengabdian Masyarakat, 2024)
Extreme poverty is a serious problem that must be addressed immediately. One effort to overcome it is by empowering local MSMEs. The presence of red brick MSMEs in Tanggung village has a positive impact on the surrounding economy. However, there is a problem of unhealthy price competition causing the economy to not run smoothly. Based on these problems, this community service aims to provide an understanding to red brick business actors to establish cooperatives that can control the price of basic necessities, the amount of stock on the market and the highest and lowest retail prices. The methods used in this study are observation and interviews. The approach used is Asset Based Community Development (ABCD) with the hope that business actors can overcome price competition by establishing cooperatives.